[Comment] Optimal bowel resection margin in colon cancer surgery: prospective multicentre cohort study with lymph node and feeding artery mapping - Dou Ruoxu; Wu Xiaolin (结直肠肛门外科)
[Background] There are no standardised criteria for the ‘regional’ pericolic node in colon cancer, which represents a major cause of the international uncertainty regarding the optimal bowel resection margin. This study aimed to determine ‘regional’ pericolic nodes based on prospective lymph node (LN) mapping. [Methods] According to preplanned in vivo measurements of the bowel, the anatomical distributions of the feeding artery and LNs were determined in 2, 996 stages Ⅰ-Ⅲ colon cancer patients who underwent colectomy with resection margin>10 cm at 25 institutions in Japan. [Findings] The mean number of retrieved pericolic nodes was 20.9 (standard deviation, 10.8) per patient. In all patients except seven (0.2%), the primary feeding artery was distributed within 10 cm of the primary tumour. The metastatic pericolic node most distant from the primary tumour was within 3 cm in 837 patients, 3-5 cm in 130 patients, 5-7 cm in 39 patients and 7-10 cm in 34 patients. Only four patients (0.1%) had pericolic lymphatic spread beyond 10 cm; all of whom had T3-4 tumours accompanying extensive mesenteric lymphatic spread. The location of metastatic pericolic node did not differ by the feeding artery’s distribution. Postoperatively, none of the 2, 996 patients developed recurrence in the remaining pericolic nodes. [Interpretation] The pericolic nodes designated as ‘regional’ were those located within 10 cm of the primary tumours, which should be fully considered when determining the bowel resection margin, even in the era of complete mesocolic excision.